Examining the association between parenting and psychosomatic problems: self-esteem as a mediator across ages in early adolescence - Amy C. O’Neill; Valerie A. Kuhlmeier; Wendy M. Craig (International Journal of Adolescence and Youth, 2019)
Supportive parenting is known to protect against psychosomatic manifestations of distress, yet the mechanisms through which this association operates are less clear. The present study evaluates children’s self-esteem as a mediator, partially explaining the association between parent–child relationship quality and psychosomatic problems from late childhood to mid-adolescence. Results from a large, nationally-representative Canadian sample indicated that self-esteem partially mediated these associations, and self-esteem accounted for more shared variance between parent–child relationship quality and psychosomatic problems among younger children. Among older children, shared variance with self-esteem explained a smaller portion of this association, but the remaining direct effect of parent–child relationship on psychosomatic problems was larger. These findings suggest that supportive parents protect against psychosomatic problems, and that they do so by promoting self-esteem for younger children and through other mechanisms as children age. Results are discussed in the context of attachment theory and age-related trends in self-esteem development.